Coffin–Siris syndrome is a SWI/SNF complex disorder. (23rd July 2013) - Tsurusaki, Y.; Okamoto, N.; Ohashi, H.; Mizuno, S.; Matsumoto, N.; Makita, Y.; Fukuda, M.; Isidor, B.; Perrier, J.; Aggarwal, S.; Dalal, A.B.; Al‐Kindy, A.; et al.
<x xml:space="preserve">Abstract</x> Coffin–Siris syndrome (CSS) is a congenital disorder characterized by intellectual disability, growth deficiency, microcephaly, coarse facial features, and hypoplastic or absent fifth fingernails and/or toenails. We previously reported that five genes are mutated in CSS, all of which encode subunits of the switch/sucrose non‐fermenting (SWI/SNF) ATP‐dependent chromatin‐remodeling complex: SMARCB1, SMARCA4, SMARCE1, ARID1A, and ARID1B. In this study, we examined 49 newly recruited CSS‐suspected patients, and re‐examined three patients who did not show any mutations (using high‐resolution melting analysis) in the previous study, by whole‐exome sequencing or targeted resequencing. We found that SMARCB1, SMARCA4, or ARID1B were mutated in 20 patients. By examining available parental samples, we ascertained that 17 occurred de novo. All mutations in SMARCB1 and SMARCA4 were non‐truncating (missense or in‐frame deletion) whereas those in ARID1B were all truncating (nonsense or frameshift deletion/insertion) in this study as in our previous study. Our data further support that CSS is a SWI/SNF complex disorder.